Should Climate Scientists Fly? A Case Study of Arguments at the System Level - Goodwin, Jean (Informal Logic, 2020)
I inquire into argument at the system level, exploring the controversy over whether climate scientists should fly. I document participants’ knowledge of a skeptical argument that because scientists fly, they cannot testify credibly about the climate emergency. I show how this argument has been managed by pro-climate action arguers, and how some climate scientists have developed parallel reasoning, articulating a sophisticated case why they will be more effective in the controversy if they fly less. Finally, I review some strategies arguers deploy to use the arguments of others against them. I argue that only by attending to argument-making at the system level can we understand how arguers come to know the resources for argument available in a controversy and to think strategically about how to use them. I call for more work on argument at the system level.